Library community engagement in the online environment: Impact, lessons identified, and way forward - Solemos, Roana Marie Flores (Animo Repository, 2022)
The primary objective of this research is to assess the online community engagement programs of the De La Salle University (DLSU) Libraries delivered during the COVID-19 pandemic. The researchers utilized a mixed-method approach to get a holistic view of the participants’ assessment. The findings of the study revealed that DLSU Libraries has been successful in implementing community engagement programs via online means despite the challenges presented by the pandemic. Though excellent in the overall program components, there has been recorded a minimal scope for improvement which can greatly help in creating a roadmap for enhancement of future community engagement efforts.